Commissioning of the new muon-to-central-trigger-processor interface at ATLAS. (1st March 2023) - Koulouris, A.; Afik, Y.; Armbruster, A.; Czodrowski, P.; Ellis, N.; Haas, S.; Kulinska, A.; Marzin, A.; Pauly, T.; Penc, O.; Perrella, S.; Ryjov, V.; et al.
Abstract: The ATLAS trigger system includes a Level-1 (L1) trigger based on custom electronics and firmware, and a high-level software trigger running on off-the-shelf hardware. The L1 trigger system uses information from the forward detectors, the calorimeters and the muon trigger detectors. Once information from all muon trigger sectors has been received, trigger candidate multiplicities are calculated by the Muon-to-Central-Trigger-Processor Interface (MUCTPI). Muon multiplicity information is sent to the Central-Trigger-Processor (CTP) and trigger objects are sent to the L1 Topological Trigger Processor (L1Topo). The CTP combines the information received from the MUCTPI with the trigger information from the forward detectors, the calorimeters and the L1Topo, and takes the L1 trigger decision. As part of the ATLAS L1 trigger system upgrade for Run-3 of the Large Hadron Collider (LHC) a new MUCTPI has been designed and commissioned. We discuss the commissioning and operation of the new MUCTPI used in ATLAS from the beginning of Run-3. In particular, we describe the integration tests which have been carried out for the commissioning and operation of the new MUCTPI.